Difference in Postural Control Between Patients With Functional and Mechanical Ankle Instability. (October 2014) - Chen, Henry; Li, Hong-Yun; Zhang, Jian; Hua, Ying-Hui; Chen, Shi-Yi
Background: Lateral ankle sprain is one of the most common injuries. Since the structural and pathological differences in mechanical ankle instability (MAI) and functional ankle instability (FAI) may not be the same, it may be better to treat these as separate groups. The purpose of this study was to compare the difference in postural sway between MAI and FAI in patients with chronic ankle instability (CAI). Methods: Twenty-six patients with CAI and 14 healthy control participants were included in the study. The CAI patients were subdivided into MAI (15 patients) and FAI (11 patients) groups. Patients who were diagnosed with lateral ankle ligaments rupture by magnetic resonance imaging and ultrasonography were assigned to the MAI group. All participants performed single-limb postural sway tests 3 times on each leg with eyes closed and open. The average distances from the mean center of pressure position in the mediolateral and anteroposterior directions were recorded and compared among the 3 groups. Results: The unstable ankles in the MAI group showed significantly greater postural sway in the anterior, posterior, and medial directions compared with those in the control group with eyes closed. With eyes open, significantly greater postural sway was found in the anterior direction. In the FAI group, no difference was found in postural sway compared with those in the control group. The MAI group showed significantly greater postural sway in the anterior direction compared with the FAI group with eyes closed and open. No significant difference in postural sway was found between the unstable and stable ankles in the MAI or FAI groups, with or without vision. Conclusions: Patients with MAI have deficits in postural control, especially in anterior-posterior directions. However, no difference was found in postural sway in patients with FAI compared with healthy people. Clinical Relevance: As MAI patients suffer from deficits in postural control, balance training should be applied in those patients. In addition, special training should also include the contralateral side after a unilateral ankle ligament injured.